Psychosocial School Conditions and Mental Wellbeing Among Mid-adolescents: Findings From the 2017/18 Swedish HBSC Study - Sara Brolin Låftman; Bitte Modin; Maria Granvik Saminathen; Viveca Östberg; Petra Löfstedt; Kristiina Rajaleid; Kristiina Rajaleid (Frontiers Media S.A., 2023)
Objectives: To investigate mid-adolescent boys' and girls' experiences of school demands, teacher support, and classmate support, and explore the associations of these factors with mental wellbeing.Methods: Data were derived from the Swedish Health Behaviour in School-aged Children (HBSC) study of 2017/18, with information collected among 1,418 students in grade 9 (∼15-16 years). School demands, teacher support, and classmate support were measured by indices based on three items each. Mental wellbeing was measured by the Short Warwick-Edinburgh Mental Wellbeing Scale (SWEMWBS). Linear regression analyses were performed.Results: Higher demands were associated with lower mental wellbeing. Conversely, mental wellbeing increased with greater teacher support and classmate support. Interactions between demands and the support variables showed that at the lowest levels of teacher and of classmate support, mental wellbeing was low and not associated with school demands. With increasing levels of teacher and classmate support, the overall level of mental wellbeing increased and revealed an inverse association between school demands and mental wellbeing.Conclusion: The study contributes with knowledge about how psychosocial conditions in school may hinder or enhance wellbeing among students.